Methods and tools in user-centered design for information technology - Galer, Margaret; Harker, Susan; Ziegler, Jurgen (Professor of Computer Science and Applied Cognitive Science) (Human factors in information technology, 1992)
This book is concerned with the development of human factorsinputs to software design. The aim is to create products whichmatch the requirements and characteristics of users and whichoffer usable user interfaces. The HUFIT project - Human Factorsin Information Technology - was carried out within the EuropeanStrategic Programme for Research and Development in InformationTechnology (ESPRIT) with the objective of enhancing the qualityof software design within the European Community. The variety ofactivities undertaken to achieve this goal are reflected in thisbook. It describes human factors know.